SNARE and regulatory proteins induce local membrane protrusions to prime docked vesicles for fast calcium-triggered fusion - Bharat, Tanmay; Malsam, Jörg; Hagen, Wim; Malsam, Andrea; Söllner, Thomas; Briggs, John A. G. (EMBO reports, 2014)
Abstract Synaptic vesicles fuse with the plasma membrane in response to Ca2+ influx, thereby releasing neurotransmitters into the synaptic cleft. The protein machinery that mediates this process, consisting of soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs) and regulatory proteins, is well known, but the mechanisms by which these proteins prime synaptic membranes for fusion are debated. In this study, we applied large-scale, automated cryo-electron tomography to image an in vitro system that reconstitutes synaptic fusion. Our findings suggest that upon docking and priming of vesicles for fast Ca2+-triggered fusion, SNARE proteins act in concert with regulatory proteins to induce a local protrusion in the plasma membrane, directed towards the primed vesicle. The SNAREs and regulatory proteins thereby stabilize the membrane in a high-energy state from which the activation energy for fusion is profoundly reduced, allowing synchronous and instantaneous fusion upon release of the complexin clamp.